Pengaruh Kepercayaan Merek, Kualitas Pelayanan Islami, dan Promosi Terhadap Kepuasan Pelanggan Outlet Hamas di Kota Jambi - Rini Erina; Titin Agustin Nengsih; Muhammad Ismail (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This thesis aims to determine how the influence of brand trust, Islamic service quality, and promotion on customer satisfaction. Outlet Hamas Customers in Jambi City. Research Here using quantitative research methods the approach The approach used in this research is descriptive-quantitative method. The results showed (1) a Sig value of 0.000 <0.005 This means that Brand Trust has a significant effect on customer satisfaction. has a significant effect on customer satisfaction. The t-count value value of 8.510> 1.985 from the t-table. this means that brand trust has a significant effect significant effect on customer satisfaction. (2) the value of Islamic service quality Sig of 0.000 <0.005, this means that Islamic service quality has a significant effect on customer satisfaction. customer satisfaction. And it can be seen that the t-count value is 4,993 > 1,985 from the t-table, this means that Islamic service quality has a significant effect on customer satisfaction. (3) value Sig promotion value of 0.000 <0.005,. This means that promotion has a significant on customer satisfaction customer satisfaction. And it can be seen that the value of t-count of 5.773> 1.985 from the t-table,. This means that promotion has an effect on customer satisfaction. (4) Sig value value of 0.000 <0.05, this means that brand trust brand trust, Islamic service quality, and promotion simultaneously have a significant influence on customer satisfaction. together (simultaneously) have a significant influence on customer satisfaction or the fourth hypothesis is accepted. is accepted.